ЕР ОСТИ СУВЛАРИНИ МОНИТОРИНГ ҚИЛИШДА НЕЙРО-ҚАТЬИЙМАС МОДЕЛЛАШТИРИШ - Досымбетов, А.М.; Турдышов, Д.Х.; Жаксулыков, Ш. (SCIENCE and SOCIETY, 2022)
Triangular, trapezoidal methods were used in the work to determine the corresponding functions. Mamdani and Sugino's indeterminate inference algorithm was used for summing up and making decisions. The results of computational experiments performed on the basis of a neurostable groundwater monitoring model are presented in 2D, 3D graphical form using a table and the FLT environment of the Matlab package.
Keywords: mathematical modeling; indefinite set theory; indefinite neural networks; groundwater; hydrogeology; algorithm